Creativity and Religiosity: A Reanalysis with Regional Predictors. Issue 3 (3rd July 2018) - Acar, Selcuk; Runco, Mark A.; Ogurlu, Uzeyir
Abstract : Building on previous research showing a negative relationship between conservatism and creativity, the present investigation focused specifically on religiosity in the context of the United States. Because of the association between conservatism and religiosity, creativity might have a negative association with religiosity, too. To this end, individuallevel and regional data were matched by linking responses to psychometric measures such as Attitudes and Values toward Creativity to regional data such as church attendance. These analyses controlled other regional variables including education, diversity, and socio-economic status. Two-level analyses with individual data at Level 1 and county data at Level 2 indicated that people from more religious locations held less positive attitudes and values toward creativity and rated their environment as less creative. On the other hand, creative personality, ideational behavior and creative achievement were not significantly related to religiosity. Those analyses provided evidence that creativity and religiosity have a negative relationship in terms of people's attitudes and values toward creativity as well as their perceptions of environment for creativity. Findings were discussed in terms of types of religiosity and other socio-cultural variables.